Omnis enim rei inspectio etymologia cognita planior est. Etymology According to Isidore of Seville and its Exemplification in the Light of Concepts and Methods of Contemporary Polish Historical Linguistics - Chmielewska, Katarzyna; Jaros, Violetta (Studia Warmińskie, 2022)
The aim of this study is to present the figure and written legacy of St. Isidore of Seville, especially his conception of etymology and an attempt to read it in the light of concepts and methods of contemporary Polish historical linguistics. Detailed considerations will concern: a) the concept and its understanding, b) the aim of etymological investigations, c) the research procedure. The essential assumption of the Isidorian concept of etymology is the conviction of the exceptional role of language, which not only enables man to know the world, but also reflects the higher order of the universe. The procedure proposed by Sevillian and used in his compendium to explain the meaning of words is based primarily on the interpretation of names as derivative expressions and involves the construction of narrative structures in which origo and interpretatio make it possible to determine the semantic feature relevant to vis verbi.